Persepsi Guru Pamong Terhadap Pelaksanaan Praktik Pengalaman Lapangan (PPL) Mahasiswa - Moh. Zainal Fanani (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2016)
This research aims at getting a picture of guardian teachers’ perception in MTsN, MAN, and SMAN in Kediri city toward pedagogical, professional, personal and social competences of PPL students of Tarbiyah department of STAIN Kediri in 2005. The research method used is a descriptive qualitative. The findings show that the average score for pedagogical competence is 69.13 % which is included in good criteria. The average score for professional competence is 72.36 % which is included in good criteria. The average score for personal competence is 75.97 % which is included in good criteria. Furthermore, the average score for social competence is 75.09 % which is included in good criteria. Therefore, it can be concluded that the guardian teachers’ perception in MTsN, MAN, and SMAN in Kediri city toward the implementation of PPL (Praktek Pengalaman Lapangan) of Tarbiyah students of STAIN Kediri is good with average score 73.14 %.